Obesity related risk of sudden cardiac death in the atherosclerosis risk in communities study - Adabag, S.; Huxley, Rachel; Lopez, F.; Chen, L.; Sotoodehnia, N.; Siscovick, D.; Deo, R.; Konety, S.; Alonso, A.; Folsom, A. (2015)
Objective To examine the association of body mass index (BMI), waist circumference (WC) and waist hip ratio (WHR) with sudden cardiac death (SCD) in community dwelling individuals. Methods Data from a multicentre, prospective, cohort study of 14 941 men and women (African American, and white), aged 45-64 years, participating in the Atherosclerosis Risk in Communities study was analysed. Obesity measures were assessed at baseline (1987-1989). SCD was adjudicated by a committee. Results At enrolment mean±SD age of the participants was 54±6 years (55% female; 26% African American). During 12.6±2.5 years of follow-up, 253 SCD occurred (incidence rate 1.34/100 person-years). The association between obesity and SCD differed by smoking status (interaction p=0.01). In models adjusting for age, sex, race, study centre and education level, SCD risk was positively associated (p<0.001) with BMI, WC and WHR in non-smokers, but not in smokers. WHR was more strongly associated with SCD in non-smokers than was BMI or WC (HR per SD increment (95% CI) 2.00 (1.65 to 2.42); 1.34 (1.15 to 1.56) and 1.49 (1.28 to 1.74), respectively). After adjustment for potential mediators (hypertension, diabetes, lipid profile, prevalent coronary heart disease, heart failure, and LV hypertrophy), nonsmokers in the highest WHR category (>0.95 in women; >1.01 in men) had double the risk of SCD (HR 2.03, 95% CI 1.19 to 3.46; incidence rate 1.43/1000 personyears) versus those with normal WHR. Conclusions General obesity is associated with increased risk of SCD in middle-aged, non-smoking individuals, mediated by traditional cardiovascular risk factors. Central obesity, however, is independently associated with SCD by pathways that remain to be elucidated.